'An offer you can't refuse' : workfare in international perspective - Lødemel, Ivar; Trickey, Heather (Policy Press, 2001)
The product of research funded by the EU, this book compares work-for-welfare policies from the United States with overlooked examples of workfare to be found in six European countries - France, Germany, the Netherlands, Norway, Denmark and Britain.